Coupling of apoptosis and L/R patterning controls stepwise organ looping. - Suzanne, M.; Petzoldt, A.G.; Spéder, P.; Coutelis, J.B.; Steller, H.; Noselli, S. (Current Biology, 2010)
Handed asymmetry in organ shape and positioning is a common feature among bilateria, yet little is known about the morphogenetic mechanisms underlying left-right (LR) organogenesis. We utilize the directional 360° clockwise rotation of genitalia in Drosophila to study LR-dependent organ looping. Using time-lapse imaging, we show that rotation of genitalia by 360° results from an additive process involving two ring-shaped domains, each undergoing 180° rotation. Our results show that the direction of rotation for each ring is autonomous and strictly depends on the LR determinant myosin ID (MyoID). Specific inactivation of MyoID in one domain causes rings to rotate in opposite directions and thereby cancels out the overall movement. We further reveal a specific pattern of apoptosis at the ring boundaries and show that local cell death is required for the movement of each domain, acting as a brake-releaser. These data indicate that organ looping can proceed through an incremental mechanism coupling LR determination and apoptosis. Furthermore, they suggest a model for the stepwise evolution of genitalia posture in Diptera, through the emergence and duplication of a 180° LR module.